A Delphi consensus study on oral language disorder in Spanish-speaking countries - Andreu Barrachina, Llorenç; Auza, Alejandra; Coloma, Carmen Julia; Dioses Chocano, Alejandro Segundo; Lara Díaz, M. Fernanda; Maggio, Verónica; Simón-Cereijido, Gabriela; Consorcio AHITL (Revista de Investigación en Logopedia, 2026)
Oral language acquisition disorder is highly prevalent and can lead to severe and persistent difficulties throughout the lifespan. The aim of this study was to reach a consensus within the Spanish-speaking context on conceptual, classificatory, and diagnostic aspects of oral language disorder, given the existing variability in terminology and clinical criteria. To this end, a panel of 51 specialists from different Spanish-speaking countries participated in a two-round Delphi study. In the first round, 28 questions addressing terminology, subtypes, comorbidities, and diagnosis were evaluated; in the second round, 12 statements were reformulated based on the previous results. This process led to the establishment of 25 main agreements. At the terminological level, consensus was reached on the use of the term “language disorder” to refer to persistent difficulties affecting communicative development, and “developmental language disorder (DLD)” when no identifiable biomedical cause is present. The creation of formal subtypes was rejected, and a detailed description of the affected linguistic domains was recommended. It was also agreed that certain biomedical conditions exclude a diagnosis of DLD, although DLD may co-occur with other disorders. Regarding diagnosis, the need for a comprehensive, multidimensional assessment based on clinical and functional criteria was emphasized, allowing the identification of severe and persistent difficulties from four years of age onwards. These agreements represent a significant step toward the unification of criteria in the Spanish-speaking field.
Keywords: Delphi; Developmental language disorder; Spanish speakers; Specific language impairment